Impact of Subsidy Removal on Tertiary Education in Nigeria - Niyi Jacob Ogunode; Conrad Ugochukwu Ukozor (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The removal of petrol subsidies in Nigeria has resulted in a notable escalation in the prices of goods and services, impacting both public and private sectors. This phenomenon's pervasive effects extend to tertiary institutions, which are particularly vulnerable due to the nature of their services. This research paper systematically examines the impact of subsidy removal on tertiary education in Nigeria. Employing a secondary data approach, information was sourced from both printed materials and online publications. The findings unequivocally demonstrate that the removal of subsidies has cast adverse ramifications on tertiary education, manifesting as amplified operational costs, elevated tuition fees, increased expenses for research initiatives, augmented outlays for infrastructure provisioning, and necessitated alterations in pedagogical delivery methods across diverse tertiary establishments nationwide. To address these challenges, the paper presents a recommendation for Federal and State governments to allocate a minimum of 20% of the monthly saved subsidy funds toward tertiary education investments countrywide, simultaneously advocating for heightened research funding.